2021
DOI: 10.3390/cells10040725
|View full text |Cite
|
Sign up to set email alerts
|

How (5′S) and (5′R) 5′,8-Cyclo-2′-Deoxypurines Affect Base Excision Repair of Clustered DNA Damage in Nuclear Extracts of xrs5 Cells? A Biochemical Study

Abstract: The clustered DNA lesions (CDLs) are a characteristic feature of ionizing radiation’s impact on the human genetic material. CDLs impair the efficiency of cellular repair machinery, especially base excision repair (BER). When CDLs contain a lesion repaired by BER (e.g., apurinic/apyrimidinic (AP) sites) and a bulkier 5′,8-cyclo-2′-deoxypurine (cdPu), which is not a substrate for BER, the repair efficiency of the first one may be affected. The cdPus’ influence on the efficiency of nuclear BER in xrs5 cells have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
52
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(79 citation statements)
references
References 44 publications
(41 reference statements)
25
52
2
Order By: Relevance
“…Moreover, in the recent article by Boguszewska et al it was shown that, for bi-stranded CDL, when the distance between (5′ S )cdA and AP-site is bigger than seven nucleotides, the activity of AP-site repair via the BER system was unchanged [ 45 ]. Additionally, this was also noted for (5′ R )cdA and both diastereomeric forms of 5′,8-cyclo-2′-deoxyguanosine (5′ S and 5′ R ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the recent article by Boguszewska et al it was shown that, for bi-stranded CDL, when the distance between (5′ S )cdA and AP-site is bigger than seven nucleotides, the activity of AP-site repair via the BER system was unchanged [ 45 ]. Additionally, this was also noted for (5′ R )cdA and both diastereomeric forms of 5′,8-cyclo-2′-deoxyguanosine (5′ S and 5′ R ).…”
Section: Resultsmentioning
confidence: 99%
“…This study showed the potential of cdPus to diminish RE activity. Since it is known that cdPus may affect eukaryotic DNA repair [ 11 , 13 , 14 ], it is advisable to investigate the impact of cdPus on the maintenance of the bacterial genome in more detail. Moreover, current findings on the influence of cdPus on eukaryotic DNA repair are based on research performed in vitro or using pure enzymes [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since it is known that cdPus may affect eukaryotic DNA repair [ 11 , 13 , 14 ], it is advisable to investigate the impact of cdPus on the maintenance of the bacterial genome in more detail. Moreover, current findings on the influence of cdPus on eukaryotic DNA repair are based on research performed in vitro or using pure enzymes [ 13 , 14 ]. Studies on bacterial models may lead to a further in vivo approach to unveil the mechanism of cdPus action [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations